Development of Inventory Management System for Small and Medium Enterprises Using Client-Server Architecture - Janice Jane C. Flores-Alhaddad; Jojo Reyes (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Small and Medium Enterprises (SMEs) constitute the structural core of the Philippine economy, yet a disproportionate number continue to manage inventory through manual or semi-manual processes—paper logs, ledgers, and spreadsheets that introduce chronic inaccuracies, obscure stock visibility, and produce the kind of unreliable data on which poor business decisions are made. This study details the design, development, and evaluation of a custom Inventory Management System (IMS) built on client-server architecture and tailored specifically for resource-constrained SMEs. The server centralizes data storage through a normalized relational database, while client applications provide intuitive interfaces for real-time inventory tracking, transaction processing, automated low-stock alerts, and report generation. The development stack was selected for cost-effectiveness and local deployability: PHP/Laravel or Node.js for backend logic, MySQL or PostgreSQL for the database layer, and a responsive web front end built with HTML, CSS, JavaScript, and Bootstrap 5, with multi-user access governed by role-based access control (RBAC). Development followed the Waterfall model enhanced with iterative prototyping, informed by surveys and interviews with 15 SME owners and managers in Metro Manila and surrounding provinces. Evaluation across simulated and live SME environments yielded measurable performance gains: inventory accuracy improved from 78% to 97.3%, stockout incidents decreased by 45%, and time spent on inventory-related tasks was reduced by more than 60%, with report generation compressed from one to two hours to under ten seconds. The system was designed with the operational realities of Philippine SMEs explicitly in mind—limited IT infrastructure, intermittent internet connectivity, and sustained pressure to minimize technology costs—and supports on-premises or hybrid deployment as a deliberate alternative to recurring-cost cloud subscriptions. These findings contribute to the growing body of literature on practical digital solutions for micro, small, and medium enterprises in developing-country contexts, and offer a replicable model for SME digitalization in similarly constrained environments across Southeast Asia.